2007
DOI: 10.1590/s1807-59322007000400010
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Factors Prior to Cataract Surgery

Abstract: PURPOSE:Identification of emotional factors related to daily difficulties and surgical treatment among patients with cataract at a university hospital. METHODS: A cross-sectional study was carried out by means of a questionnaire, elaborated based on a previous study. The sample consisted of patients seen at the cataract unit of the ophthalmology clinic of a university hospital. RESULTS: The sample consisted of 110 individuals of both sexes (34.5% men; 65.5% women) between the ages of 43 and 89 (average 69.0 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
16

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 10 publications
2
40
0
16
Order By: Relevance
“…Former studies confirmed that cataract surgery patients often experience fear and anxiety [3][4][5] not only during but also before and after the operation, and during post-operative visits [6,7]. The consequences of high perioparative anxiety range from increased pain sensitivity [2], blood pressure and heart rate [8], medication requirement [9], and reduced compliance during the procedure [10].…”
Section: Introductionmentioning
confidence: 99%
“…Former studies confirmed that cataract surgery patients often experience fear and anxiety [3][4][5] not only during but also before and after the operation, and during post-operative visits [6,7]. The consequences of high perioparative anxiety range from increased pain sensitivity [2], blood pressure and heart rate [8], medication requirement [9], and reduced compliance during the procedure [10].…”
Section: Introductionmentioning
confidence: 99%
“…(11,12) Studies show that personal beliefs, such as the "fear of going blind," "fear of dying during surgery," "fear of pain," and "fear of anaesthesia," added to the lack of knowledge about the surgical procedure and its complications, lead to a delay in the demand for cataract surgery. (11,12) The complication most feared by surgeons is endophthalmitis, which can lead to poor visual results and even vision loss.…”
Section: Discussionmentioning
confidence: 99%
“…(11,12) Studies show that personal beliefs, such as the "fear of going blind," "fear of dying during surgery," "fear of pain," and "fear of anaesthesia," added to the lack of knowledge about the surgical procedure and its complications, lead to a delay in the demand for cataract surgery. (11,12) The complication most feared by surgeons is endophthalmitis, which can lead to poor visual results and even vision loss. (1)(2)(3)(4)(5)(6)(7)(8)(9) Considering that senile cataract is the leading cause of blindness worldwide (13)(14)(15) and the growing elderly population, outpatient procedures are an important tool in ophthalmology.…”
Section: Discussionmentioning
confidence: 99%
“…Estimativas apontam que, para o Brasil compensar o surgimento de novos casos de catarata, seria necessária a realização de cerca de 500 mil cirurgias por ano. Segundo dados do Ministério da Saúde, foram realizadas em 2002, pelo sistema público de saúde, aproximadamente 300.000 cirurgias de catarata, quantidade insuficiente para a necessidade nacional (2) .…”
Section: Importância Do Centro Cirúrgico Ambulatorial Para a Realizaçunclassified
“…-promoção de cirurgia economicamente acessível (2)(3)(4)(5)(6)(7)(8)(9) ; -oferta de cirurgia de boa qualidade, que proporcione resultados satisfatórios, utilizando novas tecnologias, e estimule a procura pelo tratamento (2,(10)(11)(12)(13)(14)(15)(16)(17)(18) .…”
Section: Importância Do Centro Cirúrgico Ambulatorial Para a Realizaçunclassified